KONFIGURASI SPASIAL GAPURA PADURAKSA, KELIR, DAN PAGER DI KOMPLEKS MASJID DAN MAKAM RAJA MATARAM KOTAGEDE - Feri Setiyanto (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
The Kotagede Mosque and Royal Tomb Complex represents Javanese–Islamic vernacular architecture, showcasing a synthesis of religious, social, and symbolic functions. This study examines the spatial configuration of gapura paduraksa, kelir, and pager as architecture element in forming the hierarchical sacred space of the complex. A qualitative-descriptive method was employed with morphological and phenomenological approaches through field observation, visual documentation, and interviews. The results indicate that these three elements function as boundaries and transitional spaces guiding users from profane to sacred zones, resulting in five spatial layers (mosque, bangsal dudha, bangsal pengapit, sendang seliran, and royal tomb) that philosophically represent the relationship between Habluminallah and Habluminannas. Architectural forms and ornaments reflect the cultural acculturation between Hindu–Buddhist and Islamic values typical of the Mataram era.